Downregulation of miR-193a-3p is involved in the pathogenesis of hepatocellular carcinoma by targeting CCND1 - Wang, Shi-shuo; Huang, Zhi-guang; Wu, Hua-yu; He, Rong-quan; Yang, Li-hua; Feng, Zhen-bo; Dang, Yi-wu; Lu, Hui-ping; Fang, Ye-ying; Chen, Gang (PeerJ, 2020)
Background Hepatocellular carcinoma (HCC) is the second-highest cause of malignancy-related death worldwide, and many physiological and pathological processes, including cancer, are regulated by microRNAs (miRNAs). miR-193a-3p is an anti-oncogene that plays an important part in health and disease biology by interacting with specific targets and signals. Methods In vitro assays were performed to explore the influences of miR-193a-3p on the propagation and apoptosis of HCC cells. The sequencing data for HCC were obtained from The Cancer Genome Atlas (TCGA), and the expression levels of miR-193a-3p in HCC and non-HCC tissues were calculated. The differential expression of miR-193a-3p in HCC was presented as standardized mean difference (SMD) with 95% confidence intervals (CIs) in Stata SE. The impact of miR-193a-3p on the prognoses of HCC patients was determined by survival analysis. The potential targets of miR-193a-3p were then predicted using miRWalk 2.0 and subjected to enrichment analyses, including Gene Ontology (GO) annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and Protein-Protein Interaction (PPI) network analysis. The interaction between miR-193a-3p and one predicted target, Cyclin D1 (CCND1), was verified by dual luciferase reporter assays and Pearson correlation analysis. Results MiR-193a-3p inhibited the propagation and facilitated the apoptosis of HCC cells in vitro. The pooled SMD indicated that miR-193a-3p had a low level of expression in HCC (SMD: −0.88, 95% CI [−2.36 −0.59]). Also, HCC patients with a higher level of miR-193a-3p expression tended to have a favorable overall survival (OS: HR = 0.7, 95% CI [0.43–1.13], P = 0.14). For the KEGG pathway analysis, the most related pathway was “proteoglycans in cancer”, while the most enriched GO term was “protein binding”. The dual luciferase reporter assays demonstrated the direct interaction between miR-193a-3p and CCND1, and the Pearson correlation analysis suggested that miR-193a-3p was negatively correlated with CCND1 in HCC tissues (R = − 0.154, P = 0.002). Conclusion miR-193a-3p could suppress proliferation and promote apoptosis by targeting CCND1 in HCC cells. Further, miR-193a-3p can be used as a promising biomarker for the diagnosis and treatment of HCC in the future.
Keywords: Mir-193a-3p; Hepatocellular Carcinoma; Cyclin D1; Cell proliferation; Apoptosis; Bioinformatics